Performance of LoRa SX1278 Using Yagi Antenna - Akhmad Nawawi; Ayusta Lukita Wardani; Aditya Chandra Hermawan (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
Long-distance communication with LoRa SX1278 faces challenges in range and signal quality, particularly in rural and urban environments. Standard spiral antennas often suffer from limited coverage and weak signal strength, especially over extended distances. To address these issues, this research explores a modified Yagi antenna with impedance matching to enhance the range and signal quality of LoRa SX1278 transceivers. This study provides empirical evidence that the modified Yagi antenna significantly outperforms the standard spiral antenna in transmission range and signal strength. The methodology involved testing the antennas at three different locations under horizontal conditions, focusing on comparing RSSI values and signal reception quality at varying distances. The results showed that the Yagi antenna achieved better coverage and signal strength, successfully transmitting signals up to 6250 meters. While the RSSI difference between the antennas was minor at shorter distances, the spiral antenna performed poorly in reception quality. The Yagi antenna maintained more stable signal strength over longer distances due to its effective electromagnetic energy focus. In conclusion, the Yagi antenna with impedance matching significantly enhances LoRa communication range and signal quality, particularly over longer distances.